CMIS and Apache Chemistry in action - Müller, Florian (Manning Publications, 2013)
Annotation
Online resource; title from cover (Safari, viewed Oct. 1, 2013)
Keywords: Apache (Computer file : Apache Group); Management information systems; Systèmes d'information de gestion; Engineering & Applied Sciences; Computer Science